ENT 600 : Sani Express / Fatin Azirah Mohd, Fatin Farhana Awang Shukor and Nur Liyana Samshir - Mohd Shukor, Fatin Azirah; Awang, Fatin Farhana; Samshir, Nur Liyana (2018)
This case study was conducted to examine problem that encountered by Sani Express during their business operation for the past eleven years. From this case study, we were able to make a few recommendations in order for them to improve the quality of services. The finding draws attention to the fact that problem in Sani Express Shah Alam shows some major and minor problems. Firstly, there is difficulty in purchasing online ticket through Sani Express official website. The passengers have to buy the ticket at the counter instead of purchase it online. Next, Sani Express is also poor in marketing strategy. They do not always update their promotion and advertisement about their services especially on social media. In a conclusion, this case study will shows problem associated with Sani Express Shah Alam and concludes that it would be an ideal recommendation in order for them to improve their services.